2011
DOI: 10.1002/sia.3416
|View full text |Cite
|
Sign up to set email alerts
|

Massive clusters: Secondary emission from qkeV to qMeV. New emission processes? New SIMS probe?

Abstract: We report on the secondary ion emission under massive cluster (from 100 to 1600 atoms) impacts from different organic samples. The study has been preformed at the Orsay Tandem Accelerator equipped with a Liquid Metal Ion Source (LMIS) using a time of flight (ToF) mass spectrometer (MS) with a multianode localization detector. The influence of the projectile mass and energy is studied in order to investigate the new hydrodynamic regime of the solid-particle interaction related to the use of these massive cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…A new way was thus opened to increase the molecular ion emission yields by a factor 1000 compared to those obtained by the bombardment with an atomic projectile16 at low energy. Moreover, the damage cross‐section measurements for different cluster beams including massive clusters show clearly a low damage cross‐section for Au 400 4+ ,16 and the ratio between the molecular ion emission yield and damage cross‐section increases with the energy and the mass of the cluster 17. Recently, a study of the influence of the projectile energy from 20 qkeV to 4 qMeV18 permits to reach ion emission rates higher than a few tens of molecular ions per impact.…”
Section: Introductionmentioning
confidence: 99%
“…A new way was thus opened to increase the molecular ion emission yields by a factor 1000 compared to those obtained by the bombardment with an atomic projectile16 at low energy. Moreover, the damage cross‐section measurements for different cluster beams including massive clusters show clearly a low damage cross‐section for Au 400 4+ ,16 and the ratio between the molecular ion emission yield and damage cross‐section increases with the energy and the mass of the cluster 17. Recently, a study of the influence of the projectile energy from 20 qkeV to 4 qMeV18 permits to reach ion emission rates higher than a few tens of molecular ions per impact.…”
Section: Introductionmentioning
confidence: 99%
“…Recent efforts have focused on the use of higher energy and larger cluster projectiles (e.g., C 60 and Au 400 ) to increase the secondary ion signal. 2528 …”
Section: Introductionmentioning
confidence: 99%
“…[16] Such simulations as well as experimental results have shown that molecular ion emission occurs from the rim of the impact crater resulting in ions with internal energies sufficiently low that they survive for analysis. [17,18] …”
Section: Resultsmentioning
confidence: 99%